1998
DOI: 10.1103/physrevlett.81.77
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Emission of Organic Molecules Embedded in a Photonic Crystal

Abstract: We report on modification of the spontaneous emission of dye molecules embedded in a threedimensional solid-state photonic crystal exhibiting a stop band in the visible range. Molecules embedded in artificial opal filled with a polymer show a dip in the fluorescence spectrum and nonexponential spontaneous decay kinetics containing both accelerated and inhibited components compared to the dye fluorescence in a reference polymer matrix. Results are interpreted in terms of redistribution of the photon density of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
199
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(209 citation statements)
references
References 32 publications
9
199
0
1
Order By: Relevance
“…[4][5][6][7][8][9] The observed lifetime is generally composed of two parts: one is due to the spontaneous emission of electronic excited states, the other is caused by other nonradiative internal processes in molecules. The corresponding decay rates can be denoted as ⌫ϭ1/ r and 1/ nr , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8][9] The observed lifetime is generally composed of two parts: one is due to the spontaneous emission of electronic excited states, the other is caused by other nonradiative internal processes in molecules. The corresponding decay rates can be denoted as ⌫ϭ1/ r and 1/ nr , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Martorell and Lawandy reported the first observation of inhibited spontaneous emission ͑SE͒ of dye molecules in dilute colloidal crystals composed of polystyrene microspheres in water. 4 They found a single exponential decay of the excited state and a variation of the fluorescence lifetime of 1.75 times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Passive reflection, diffraction and transmission measurements have recently been carried out in twodimensional photonic crystal structures. 8 Martorell and Lawandy, 9 and subsequently Petrov et al 10 have observed inhibited spontaneous emission from low-index contrast three-dimensional periodic structures (⑀ r ϭ1.45). Berggren et al 11 have also made active devices by including a low index contrast two-dimensional periodicity.…”
Section: ͓S0003-6951͑99͒01611-3͔mentioning
confidence: 99%
“…Note that, conceptually, with C 1 playing the role of a microscope, there is an analogy between the correlation of the fluctuations and the experimental setup [24][25][26], in which the source of light is located inside the crystal and the directionality of the outgoing light is studied. On the contrary, the long-range contributions [2,3] to the intensity correlator come from scattering trajectories that explore all directions inside the crystal, and, due to isotropization, do not carry information about the Bragg directions.…”
mentioning
confidence: 99%